The relationship between technostress creators and job satisfaction among administrative staff at Pejabat Residen and Daerah Bahagian Samarahan / Siti Nur Shafinas Paukan - Paukan, Siti Nur Shafinas (2017)
Due to the changes in technology, it has affected the users. Technology is designed to help the user; unfortunately, it has caused problems and stress to the users. Technostress happened due to rapid changes in computer technologies and it may increase user’s job satisfaction. This study was conducted to investigate the relationship between technostress creators and job satisfaction among administrative staff at Pejabat Residen and Daerah Bahagian Samarahan. The study will contribute to the extent of management and worker’s behavioral. The study will contribute to the extent of management and worker’s behavioral. Questionnaires have been used as an instrument to find out the information from the respondents. Besides that, Statistical Package for the Social Science (SPSS) has been used for the data analysis process. The result showed that Technostress which consists of Techno-Overload (r=.235*, p<.05) Techno-Invasion (r=.176*, p<.05) and Techno-Uncertainty (r=.264*, p<.05) were positively correlated with their Job Satisfaction at Pejabat Residen and Daerah Bahagian Samarahan.